Hurry Up, We Need to Find the Key! How Regulatory Focus Design Affects Children’s Trust in a Social Robot - Calvo-Barajas, Natalia; Elgarf, Maha; Perugia, Giulia; Paiva, Ana; Peters, Christopher; Castellano, Ginevra (Frontiers in Robotics and AI, 2021)
In educational scenarios involving social robots, understanding the way robot behaviours affect children's motivation to achieve their learning goals is of vital importance. It is crucial for the formation of a trust relationship between the child and robot so that the robot can effectively fulfill its role as a learning companion. In this paper we investigate the effect of a regulatory focus design scenario on the way children interact with a social robot. Regulatory Focus Theory is a type of self-regulation that involves specific strategies in pursuit of goals. It provides insights into how a person achieves a particular goal, either through a strategy focused on "promotion'' that aims to achieve positive outcomes, or one focused on "prevention'' that aims to avoid negative outcomes. In a user study, 69 children (7-9 years old) played a regulatory focus design goal-oriented collaborative game with the EMYS robot. We assessed children's perception of likability, competence, and trust in the robot, as well as their willingness to follow the robot's suggestions when pursuing a goal. Results showed that children perceived the prevention-focused robot to be more likable than the promotion-focused robot. We observed that a regulatory focus design did not directly affect trust. However, the perception of likability and competence were positively correlated with children's trust, but negatively correlated with children's acceptance of the robot's suggestions.